Analysis of student usage of online videos in synchronous and asynchronous mathematics courses - Roman, Melea R. (Kansas State University, 2022)
The push toward online learning in response to the Covid-19 pandemic has provided an opportunity to evaluate student behavior and outcomes in asynchronous and synchronous mathematics courses with an unprecedented population of students. In this study, data is collected from Canvas tracking student utilization of lecture videos. This data is analyzed under the lens of principal component analysis and partitioning around medoids to cluster students into behavioral groups. This data is then compared with grade outcomes to provide insight into possible behavioral best-practice for asynchronous and synchronous online learning in Elementary Differential Equations and History of Mathematics courses.
Keywords: Educational data mining; Online learning; Mathematics education